Examining the ability of palm kernel shell extract to control corrosion and assess its economic value on thermo-mechanically treated steel in artificial seawater: a sustainable and environmentally friendly approach - Sanni, Omotayo; Ren, Jianwei; Jen, Tien-Chien (Frontiers in Chemistry, 2024)
Each year, the rising demand for palm oil generates large amounts of palm kernel shell waste. Discarded palm kernel shells can produce activated carbon, crushed shells, liquified fumes, and other derivatives; however, their indiscriminate disposal persists, raising issues related to the environment and economy. Therefore, the purpose of this study is to investigate the use of palm kernel shell as a corrosion inhibitor for thermo-mechanically treated steel in a seawater environment using gravimetric and electrochemical techniques, as well as surface tests at varying concentrations. The findings demonstrated that the palm kernel shell inhibited the cathodic and anodic processes by adsorption on the steel surface, which followed the Langmuir adsorption isotherm. The inhibitor exhibited a 98% inhibitory efficiency at 500 ppm concentration. Scanning electron microscopy analysis verified the thin films of the inhibitor on steel surface in seawater solution. Fourier transform infrared spectroscopy results show that the extract’s components prevent the steel corrosion through an adsorptive mechanism. According to the inhibitor economic evaluation, employing the palm kernel shell extract is less expensive than utilizing conventional inhibitors.